Enhanced Healing of Cutaneous Burn Wounds in Diabetic Rats: with the administration of β-glucans Having Dual Significant Properties- Antioxidant Effects and Phenotypic Transition - Ahsan Elahi, Shan Ur Rehman, Attiq Ur Rehman, Rabia Akbar, Fouzia Jaffar, Merub Ayyub, Hafiza Sobia Ramzan, Shahrukh Awan (Pakistan Journal of Medical & Health Sciences, 2023)
The aim of this study was to evaluate the effects of β-Glucans obtained from Saccharomyces cerevisiae on the wound healing process in diabetic rats induced with streptozotocin. The investigation evaluated multiple wound healing parameters, such as the closure of the wound, alongside the assessment of CD68 and CD163 proteins, which function as indicators for M1 and M2 macrophages, respectively. The study also investigated the effects of β-Glucans on inflammatory markers, specifically IL-6 and IL-10. Additionally, the researchers analysed hydroxyproline and hexosamine levels, and performed histopathological examinations. The current study examined the anti-inflammatory effects by employing the paw edoema and cotton pellet induced granuloma methods. The findings of this study suggest that β-Glucans exhibit therapeutic properties that may have potential benefits in the treatment of burn injuries among individuals diagnosed with diabetes. These substances facilitate expedited healing of burn wounds, augment tensile strength, and exhibit properties that combat oxidation and inflammation. In addition, β-Glucans have been shown to enhance the levels of tissue hydroxyproline and hexosamine, leading to the enhancement of collagen synthesis and the development of the extracellular matrix in burn wounds of individuals with diabetes. Importantly, -Glucans have a beneficial impact on the inflammatory stage of burn wound healing without inhibiting the generation of pro-inflammatory mediators, particularly interleukin-6 (IL-6). By increasing production of the anti-inflammatory mediator interleukin-10 (IL-10), they also aid in the proliferation process. By increasing CD163 expression and decreasing CD68 expression, the research showed that -Glucans had a substantial effect in promoting the switch from the M1 to M2 phenotype at the appropriate moment. The end result is faster recovery from burn injuries in diabetic rats. Overall, the results support beta-glucans' therapeutic potential in the effective management of burn wounds in diabetic patients. Keywords: β-Glucans, Diabetic burn wound, Biochemical analysis, Phenotypic Transition, Western blot analysis, wound healing,